The elasticity of taxable income in Spain: 1999-2014 - Miguel Almunia; David López Rodríguez (SERIEs - Journal of the Spanish Economic Association, 2019)
We study how taxable income responds to changes in marginal tax rates, using as a main source of identifying variation three large reforms to the Spanish personal income tax implemented in the period 1999-2014. The most reliable estimates of the elasticity of taxable income (ETI) with respect to the net-of-tax rate for this period are between 0.45 and 0.64. The ETI is about three times larger for self-employed taxpayers than for employees and larger for business income than for labor and capital income. The elasticity of broad income is smaller, between 0.10 and 0.24, while the elasticity of some tax deductions such as the one for private pension contributions exceeds one. Our estimates are similar across a variety of estimation methods and sample restrictions and also robust to potential biases created by mean reversion and heterogeneous income trends.
Keywords: H24; H31; D63; 330; Elasticity of taxable income; ETI; Personal income tax; Mean reversion; Tax deductions; Spain